Dipole localization - Ho, Zi Hao. (2010)
The brain is a complex organ that can be found in a human being. It functions as the command centre of the human body and is responsible for functions such as breathing, regulating the body temperature thinking, learning and almost any other activity quintessential to a person’s survival.